FACTORS RELATED TO THE IMPLEMENTATION OF EARLY BREASTFEEDING (IMD) IN THE WORKING AREA OF PUSKESMAS TELUK DALAM SIMEULUE DISTRICT, 2020 - Ayu Lestari (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Early Initiation of Breastfeeding (IMD) is the process of placing the baby on the mother's chest for at least 1 hour or until the baby is successfully breastfeed. The coverage of the implementation of Early Breastfeeding Initiation (IMD) in 2019 nationally reached 71.17%, IMD coverage for Simeulue Regency in 2019 reached 35.5%, while at Teluk Dalam Health Centre (Puskesmas) it was 34.3%. This study aims to determine what factors can influence the implementation of IMD in the working area of the Teluk Dalam Puskesmas, Simeulue Regency in 2019. Metods: The research design is descriptive analytic with a cross sectional design. The sampling technique used is random sampling or random sampling of 63 respondents. The measuring instrument uses a questionnaire that has been tested for validity and reliability. Data analysis using chi square test with computer program SPSS 22. Result: The results of this study showed that there was a relationship between delivery methods, physical fatigue, gestational age, birth weight, knowledge, family support, and the role of health workers with the implementation of IMD with a significance value (p 0.05). Recommandation: From the results of this study, it is hoped that health workers will further increase awareness of the importance of implementing IMD to fulfill children's rights in getting the best intake from an early age and it is hoped that further researchers will conduct research on other factors or relationships and influences that can affect the implementation of IMD and a larger sample size.